Effects of organic zinc on the performance and gut integrity of broilers under heat stress conditions - Abuajamieh, Mohannad (Arch Anim Breed, 2020)
Heat stress (HS) has negative impacts on farm animals. Many studies have been conducted in order to ameliorate the effects of heat stress in farm animals. The current project investigated the effects of organic zinc supplementation under thermoneutral and heat stress conditions on the production, physiological, and histological parameters in broiler chickens. Three-hundred and sixty chicks in the current project were assigned randomly to six different treatments ([Formula: see text] chicks per treatment). The treatments were (1) a basal diet containing 40 mg kg [Formula: see text] of Zn from an organic source and rearing under thermoneutral (TN) conditions (Ctrl); (2) a diet containing the amount of Zn from the basal diet [Formula: see text]  % of the Zn level (from the basal diet) and rearing under TN conditions (50 TN); (3) a diet containing the amount of Zn from the basal diet [Formula: see text]  % of the Zn level (from the basal diet) and rearing under TN conditions (100 TN); (4) a basal diet containing 40 mg kg [Formula: see text] of Zn from an organic source and exposure to 3 d of cyclical HS at the age of 35 d (CHS); (5) a diet containing the amount of Zn from the basal diet [Formula: see text]  % of the Zn level (from the basal diet) and exposure to 3 d of cyclical HS at the age of 35 d (50 HS); and (6) a diet containing the amount of Zn from the basal diet [Formula: see text]  % of the Zn level (from the basal diet) and exposure to 3 d of cyclical HS at the age of 35 d (100 HS). Our results indicated that HS has decreased final body weight (fBW), average daily gain (ADG), and feed conversion ratio (FCR) relative to TN chicks. However, organic zinc had little or no effects on the production parameters measures in the current project. Overall, intestinal histological measurements were negatively altered under HS relative to TN chicks. Organic zinc inclusion in the diet had improved villus height in the duodenum and jejunum relative to the Ctrl and CHS chicks. Blood calcium and glucose levels were decreased and increased, respectively, in HS relative to TN chicks. In summary, the results discussed in the current project revealed that the inclusion rates of organic zinc used here had little or no effects on the productive parameters. However, it improved the morphological characteristics of the intestines which might maximized the intestinal efficiency in nutrient absorption under HS conditions.